KONSEP MANUSIA DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM (Studi Komparatif Pemikiran Ibn Sina dan Al-Ghazali) - Ali Rahmat (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
Human being could be considered a topic of discussion which is never completed. Therefore, this study will focus more on the concept of human in the perspective of Ibn Sina and al-Ghazali. In the perspective of Ibn Sina the essence of human being is composed of two elements, namely the body (jism) and soul (nafs). These two elements are really different from the ones found in animals and plants. The presence of soul (nafs) is its manifestation. While the body (jism) a tool for nafs. In addition, there is also a strong relationship between the jism and the nafs. Nafs will never achieve a phenomenal stage without the body. When this phenomenal stage is reached, then the nafs will rule the body. Meanwhile, according to al-Gazali the essence of human is composed of several elements, such as: al-nafs, al-ruh, al-qalb, and al-'aql. These four elements have their own function and role, but are mutually complementary parts in shaping the human personality so-called Insan Kamil. The difference of faculties possessed by human is what makes human being the noblest in the sight of Allah. The purpose of human life is to achieve happiness. Education could be considerably successful for being capable of organizing the learning process in producing quality individuals. Thus, in order to produce the quality individuals, then teachers should be able to cultivate a variety of potential possessed by each student as a human being.Keywords: Human being, education, philosophy